Circe and Rome. The Origin of the Legend - Zalewska-Jura, Hanna (Studia Ceranea, 2018)
Circe is associated first of all with the episode narrated in the 10th book of the Odyssey, in which she turns Odysseus’s crewmen into pigs using her herbal pharmaka. Odysseus survives due to divine help, his inborn cleverness, and the miraculous herb moly. The fairy-tale theme of the spells of Circe, clearly showing its folk provenance, got entrenched in ancient literature: featured most often in poems of playful content, Circe symbolized the power to subjugate male souls and bodies. From the Hellenistic era to the Byzantine times, however, Circe is mentioned in scholarly works – in the context of the history of Roman Italy. The aim of the present article is, first of all, to analyse the Greek-language source texts and show the ways in which ancient authors managed to connect a character from a folk fairy tale – intrinsically different in form and not identifiable with any heroic myth – with the prehistory of Roman Italy, and even place her among the ancestors of Rome. The considerations also allow us to identify some of the mechanisms of the creation and functioning of the legend as a cultural phenomenon of the ancient world.